2009
DOI: 10.1074/jbc.m109.006403
|View full text |Cite
|
Sign up to set email alerts
|

BRI3 Inhibits Amyloid Precursor Protein Processing in a Mechanistically Distinct Manner from Its Homologue Dementia Gene BRI2

Abstract: Alzheimer disease (AD) is characterized by senile plaques, which are mainly composed of ␤ amyloid (A␤) peptides. A␤ is cleaved off from amyloid precursor protein (APP) with consecutive proteolytic processing: ␤-secretase, followed by ␥-secretase. Here, we show that BRI3, a member of the BRI gene family that includes the familial British and Danish dementia gene BRI2, interacts with APP and serves as an endogenous negative regulator of A␤ production. BRI3 colocalizes with APP along neuritis in differentiated N2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 44 publications
1
42
1
Order By: Relevance
“…(J) Densitometry values showed no difference in prefibrillar oligomers between WT and Bri2 +/− mice. Average value for WT samples was arbitrarily equaled to 100. duction (11,16,(25)(26)(27)(28). Although we did not detect alterations in Aβ or toxic oligomers levels in FDD KI/+ mice, it is possible that synaptotoxic ADan and/or Aβ oligomers may augment in anatomically restricted locations and/or increase transiently during memory acquisition/consolidation.…”
Section: Discussioncontrasting
confidence: 42%
“…(J) Densitometry values showed no difference in prefibrillar oligomers between WT and Bri2 +/− mice. Average value for WT samples was arbitrarily equaled to 100. duction (11,16,(25)(26)(27)(28). Although we did not detect alterations in Aβ or toxic oligomers levels in FDD KI/+ mice, it is possible that synaptotoxic ADan and/or Aβ oligomers may augment in anatomically restricted locations and/or increase transiently during memory acquisition/consolidation.…”
Section: Discussioncontrasting
confidence: 42%
“…In contrast, mutations in APP and in genes that regulate APP processing, such as PSENs and BRI2/ITM2B, cause familial dementias (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). APP is cleaved by ␤-secretase/BACE1 into a soluble ectodomain (soluble APP␤) and the COOH-terminal fragment ␤-CTF.…”
mentioning
confidence: 99%
“…It was shown that the dementia gene BRI2 was an inhibitor of APP processing [29,30] and that BRI3, a member of the same gene family, was able to bind APP and to inhibit the production of Ab [31]. BRI gene family products that comprise also BRI1, are type II transmembrane (TM) proteins containing a BRICHOS domain.…”
Section: Discussionmentioning
confidence: 99%